THE EFFECT OF GROSS DOMESTIC PRODUCT, EXPORTS, IMPORTS, EXCHANGE RATES, INFLATION AND EXTERNAL DEBT ON INDONESIA'S FOREIGN EXCHANGE RESERVES IN 2017-2020 (STUDY FROM AN ISLAMIC PERSPECTIVE) - Alda Heriyatma; Elok Fitriani Rafikasari; Moh Farih Fahmi (Fakultas Syariah IAIN Kediri, 2022)
Indonesia is a country that cannot be separated from international relations. In addition, it also has a major influence in the event iof fluctuations in the world economy caused by adopting an open economic system. By conducting international relations, of course, it can increase foreign exchange reserves which of course provide benefits for the country. Indonesia itself has little foreign exchange reserves available because it is used to pay off the government's foreign debt and high import costs. If a country makes foreign loans continuously, the amount of foreign exchange reserves will decrease, so that the economy becomes sluggish. The purpose of this study was to analyze the effect of gross domestic product, exports, imports, exchange rates, inflation and foreign debt on Indonesia's foreign exchange reserves. The sample in this study is 48 data from 2017-2020. This research method is a quantitative approach with data analysis using classical assumption test, multiple linear regression analysis, hypothesis testing and coefficient of determination test with data processing test equipment, namely SPSS version 16. The results show that partially (1) gross domestic product has a positive and positive effect. significant effect on Indonesia's foreign exchange reserves, (2) exports have a positive and significant effect on Indonesia's foreign exchange reserves, (3) imports have a negative and significant effect on Indonesia's foreign exchange reserves, (4) the exchange rate has a negative and significant effect on Indonesia's foreign exchange reserves, (5) inflation does not have a significant effect on Indonesia's foreign exchange reserves, (6) foreign debt has a positive and significant effect on Indonesia's foreign exchange reserves, (7) simultaneously gross domestic product, exports, imports, exchange rates, inflation and foreign debt have a positive and significant effect on Indonesia’s foreign exchange reserves